Prognostic significance of FOXP3+ tumour-infiltrating Tregs in Egyptian breast cancer patients - Mohamed Mkayed Abdel Kader; Eman Mohamed. Saied; Safinaz Hussein. ElShourbagy; Noha Mohamed El-Anwar (Journal of the Pakistan Medical Association, 2023)
Objective: To evaluate the prognostic importance of tumour-infiltrating forkhead box P3 protein + regulatory T cells in breast cancer patients. Methods: The case-control study was conducted from January 2020 to March 2021 at the Kafrelsheikh University Hospital, Egypt, and comprised individuals with newly-diagnosed breast cancer who underwent conventional surgery,and controls who had a fibrocystic change of the breast. The density of tumour-infiltrating forkhead box P3 protein + regulatory T cells was assessed by immunohistochemistry. Overall survival and disease free-survival were assessed. Data was analysed using SPSS 25. Results: Of the 100 patients having mean age 44.9±9.1 years, 76(76%) had moderate/strong forkhead box P3 protein expression in tumour-infiltrating regulatory T cells, and 24(24%) with no/low expression. On follow-up, Patients with moderate/strong expression had a significantly greater rate of recurrence (p<0.05). Disease-free survival was substantially shorter in patients with moderate/strong expression compared to those with little or low expression (p=0.035). Compared to individuals with no/low expression, patients with moderate/strong expression had a greater rate of mortality, but the difference was not statistically significant (p>0.05). Conclusions: High density of forkhead box P3 protein + regulatory T cells in Egyptian women with breast cancer may serve as a prognostic indicator. Keywords: T-Lymphocytes, Prognosis, Immunohistochemistry, Breast neoplasms, X chromosome.